Detection of some microRNAs expressions in tissues of British Women diagnosed with Breast cancer - Saad, Zaynab (Iraqi Journal of Cancer and Medical Genetics, 2014)
MicroRNAs (miRNAs) are small, non coding RNA, found to play critical roles in tumor progression. The aim of this project was to investigate the expression of miR-21, miR-26b, miR-429 and miR-378 in human breast cancer tissues. By using TaqMan qRT-PCR assay to detect the expression of these selected miRNAs in 12 pairs of breast cancer tissues and their corresponding noncancerous breast tissues. Data indicated that the relative level of miR-21 was up regulated in cancer tissues (p 0.0014), miR-26b was significantly down regulated in breast cancer tissues (p 0.0017), While the novel expression of miR-429 was significantly up regulated in breast cancer tissues (p 0.0131) and novel down expression of miR-378 in breast cancer tissues (p 0.0006). These microRNAs might be a potential molecular biomarker for early detection of breast cancer in women